The Representation of ISIS and Iraqi Forces in Al Jazeera Arabic News Reports - Saleh Albadri, Mohammed Abed (Opción, 2019)
In recent years, the world has witnessed a number of changes that have in- fluenced the international relations and clearly reflected on most areas of life such as politics, economy, poverty, security, and the war on terror. The media whether broadcast, print, or social become an important element in evaluating the overall capacity of any country or state. In actual fact, Al Jazeera played a vital role in the positive representation of ISIS and the negative representation of Iraqi forces. By means of critical discourse analysis, this research found out that Al Jazeera ideologically concealed the negative acts of ISIS, while at the same time, highlighted the negative acts of Iraqi forces.